Array Synthetic Aperture Ladar with High Spatial Resolution Technology - Bingnan WANG; Juanying ZHAO; Wei LI; Ruihua SHI; Maosheng XIANG; Yu ZHOU; Jianjun JIA (Leida xuebao, 2022)
By extending synthetic aperture technology from the microwave band to the laser wavelength, Synthetic Aperture Ladar (SAL) has long-distance imaging and extremely high spatial resolution independent of the target distance. Presently, the small field of view is the key constraint in SAL ground observation because of the laser diffraction limitation. In this paper, an array SAL technology is proposed. With high-power array transmission, array-balanced detection, and pulse-wise dynamic internal calibration, a multichannel coherent laser transceiver is realized. Meanwhile, the field of view has multiplied. The results of turntable experiments show that the imaging resolution is better than 3 cm (distance) × 1 cm (azimuth). This technology provides a scientific and technical approach to SAL with wider swath imaging in ground observation.